Hubungan Tingkat Pendidikan dan Pekerjaan Ibu dengan Kejadian Diare Pada Balita - Ernawati, Wahyu; Dhamayanti, Reffi; Widiastini, Putu Monna Frisca (JURNAL KESEHATAN TERAPAN, 2023)
Diarrhea is accompanied by spotting fluid or liquid , more than 3 times in 24 hours. According to UNICEF (The United Nations Children's Fund) in 2019 , diarrhea is the number two cause of death in the toddler in the world. In development country only 39 % patients get serious handling. Plaju health center in 2018 there were 297 toddlers suffering diarrhea and in 2019 there is an increasing from the previous year of 541 hit diarrhea. Influencing factor of the incidence of diarrhea, among them are education, employment, the age of a toddler, environmental, nutritional, social, economic, food / drink is consumed, and the factors of lactose ( milk formula) . The purpose of this research was to find out the relationship between education and employment mother with Diarrhea in Toddlers in Plaju health center in 2023. This research use Random Sampling method using simple random sampling technique in which data concerning the independent variables (Education and Employment of mother) and dependent variables (the incidence of Diarrhea) in univariate and bivariate analysis The research results obtained are signifficant relationships between education and incidence of diarrhea in the Plaju health center Palembang in 2023 (p value = 0.045) . There is a signifficant relationship between maternal employment and incidence of diarrhea in the Plaju health center in 2023 (p value = 0.050).